Geriatric congenital heart disease: burden of disease and predictors of mortality - Afilalo, Jonathan; Therrien, Judith; Pilote, Louise; Ionescu-Ittu, Raluca; Martucci, Giuseppe; Marelli, Ariane J (Journal of the American College of Cardiology, 2011)
The study sought to measure the prevalence, disease burden, and determinants of mortality in geriatric adults with congenital heart disease (ACHD). The population of ACHD is increasing and aging. The geriatric ACHD population has yet to be characterized. Population-based cohort study using the Quebec Congenital Heart Disease Database of all patients with congenital heart disease coming into contact with the Quebec healthcare system between 1983 and 2005. Subjects with specific diagnoses of congenital heart disease and age 65 years at time of entry into the cohort were followed for up to 15 years. The primary outcome was all-cause mortality. The geriatric ACHD cohort consisted of 3,239 patients. From 1990 to 2005, the prevalence of ACHD in older adults remained constant from 3.8 to 3.7 per 1,000 indexed to the general population (prevalence odds ratio: 0.98; 95% confidence interval [CI]: 0.93 to 1.03). The age-stratified population prevalence of ACHD was similar in older and younger adults. The most common types of congenital heart disease lesions in older adults were shunt lesions (60%), followed by valvular lesions (37%) and severe congenital heart lesions (3%). Type of ACHD and ACHD-related complications had a minor impact on mortality, which was predominantly driven by acquired comorbid conditions. The most powerful predictors of mortality in the Cox proportional hazards model were: dementia (hazard ratio [HR]: 3.24; 95% CI: 1.53 to 6.85), gastrointestinal bleed (HR: 2.79; 95% CI: 1.66 to 4.69), and chronic kidney disease (HR: 2.50; 95% CI: 1.72 to 3.65). The prevalence of geriatric ACHD is substantial, although severe lesions remain uncommon. ACHD patients that live long enough acquire general medical comorbidities, which are the pre-eminent determinants of their mortality.